Relationship between Factor VII Activity and Clinical Efficacy of Recombinant Factor VIIa Given by Continuous Infusion to Patients with Factor VIII Inhibitors - Santagostino, E.; Morfini, M.; Rocino, A.; Baudo, F.; Scaraggi, F. A.; Gringeri, A. (Thrombosis and Haemostasis, 2001)
A multicenter prospective study of recombinant activated factor VII (rFVIIa) given by continuous infusion (CI) to treat severe hemorrhages and to handle surgical procedures was carried out.Relations between clinical efficacy, dosages used and levels of FVII coagulant activity (FVII:C) achieved in plasma were also evaluated. Case material included 25 patients with hemophilia (9 children and 16 adults) with high-responding inhibitors and 3 patients with acquired factor VIII inhibitors. Overall, 35 CI courses were given for 10 spontaneous bleeding episodes, 11 major surgical procedures and 14 minor surgical procedures. Bolus doses of 90 to 150 μg/kg (median: 100) were followed by CI given at median rates of 20 μg/kg/h for major surgery and of 17 and 16 μg/kg/h for minor surgery and spontaneous hemorrhages. Satisfactory hemostasis was obtained in 30 of 35 courses (88%). rFVIIa CI was ineffective in 2 hemophiliacs undergoing surgical operations and in another hemophiliac with hemoperitoneum who had to be switched to other treatments (high doses of porcine or human factor VIII concentrates). rFVIIa CI was partially effective in 2 hemophiliacs who had mild local bleeding after minor surgery. The CI rates and the corresponding FVII:C levels in plasma were similar in effective, partially effective and ineffective courses (median rate: 17, 20 and 20 μg/kg/h, respectively; median FVII:C: 14, 18 and 18 IU/ml, respectively). A single adverse event was observed, superficial thrombophlebitis. This study confirms that rFVIIa given by CI is effective in a high proportion of patients with factor VIII inhibitors. It also demonstrates that FVII:C levels attained in plasma do not always predict efficacy because similarly high levels were attained during successful treatments and in those that failed.
Keywords: rFVIIa; continuous infusion; FVII:C; inhibitor; hemophilia